Self-Compassionate Responses to an Imagined Sexual Assault - Allen, Ashley Batts (Violence against women, 2021)
This research assesses the relationship between self-compassion and well-being following an imagined trauma (i.e., sexual assault) and shows positive outcomes from a self-compassion induction. After a pilot study (N = 54) established the believability of a sexual assault scenario, the primary study randomly assigned female participants (N = 141) to a self-compassion or control condition. Participants read educational prompts (self-compassion and verbal learning or verbal learning only), completed comprehension questions, read and wrote about a hypothetical scenario from a compassionate perspective or generally, and completed the trait self-compassion scale. Regression analyses showed trait and induced self-compassion predicted less negative outcomes.